2017
DOI: 10.1001/jama.2017.7218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depth and Duration of Cooling on Death or Disability at Age 18 Months Among Neonates With Hypoxic-Ischemic Encephalopathy

Abstract: IMPORTANCE Hypothermia for 72 hours at 33.5°C for neonatal hypoxic-ischemic encephalopathy reduces death or disability, but rates continue to be high. OBJECTIVE To determine if cooling for 120 hours or to a temperature of 32.0°C reduces death or disability at age 18 months in infants with hypoxic-ischemic encephalopathy. DESIGN, SETTING, AND PARTICIPANTS Randomized 2 × 2 factorial clinical trial in neonates (≥36 weeks’ gestation) with hypoxic-ischemic encephalopathy at 18 US centers in the Eunice Kennedy S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
138
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 199 publications
(149 citation statements)
references
References 14 publications
1
138
1
1
Order By: Relevance
“…During this trial, the Neonatal Research Network initiated the Optimizing Cooling trial to study longer (120 hours) or deeper (32°C) cooling initiated at less than 6 hours of age. 36,37 The Optimizing Cooling trial was stopped early partly owing to safety concerns for increased in-hospital mortality among infants cooled for 120 rather than 72 hours. Whether the current trial results would differ if the intervention was shortened to 72 hours cannot be answered.…”
Section: Discussionmentioning
confidence: 99%
“…During this trial, the Neonatal Research Network initiated the Optimizing Cooling trial to study longer (120 hours) or deeper (32°C) cooling initiated at less than 6 hours of age. 36,37 The Optimizing Cooling trial was stopped early partly owing to safety concerns for increased in-hospital mortality among infants cooled for 120 rather than 72 hours. Whether the current trial results would differ if the intervention was shortened to 72 hours cannot be answered.…”
Section: Discussionmentioning
confidence: 99%
“…Overall there is little evidence to address the impact of cooling duration in a preterm model. Importantly, the single human study of prolonging cooling time in term HIE infants (from 3 to 5 days) did not show any long-term detrimental effect on the brain (Shankaran et al, 2017). Future studies will be needed to determine whether a shorter interval of cooling (for example the brief and mild (2 h) period of cooling used in Smith et al, 2015) might still provide benefits in a moderately premature (P6 HI) rat model.…”
Section: Duration Of Coolingmentioning
confidence: 98%
“…In addition, an observational human cooling study (6) showed that starting cooling between zero and three hours resulted in better motor outcome at 18 months than those who started cooling between three and six hours. There is also a concern that both human and experimental data suggest that longer cooling may be harmful (7,8). In the foetal sheep experiments, cooling for 120 hours was less protective than cooling for 72 hours (8).When Laptook et al provide probabilities for the relative risk parameter RR = p 1 /p 0 being less than 1, or less than 588…”
mentioning
confidence: 99%